The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12958-020-00577-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of vascular endothelial growth factor polymorphisms with polycystic ovarian syndrome risk: a meta-analysis

Abstract: Background: Polycystic ovarian syndrome (PCOS) is a multi-gene hereditary disorder caused by the interaction of certain gene variation with environmental factors. Previous studies have shown that vascular endothelial growth factor (VEGF) gene polymorphisms are associated with the risk of polycystic ovarian syndrome. However, the results of these studies remain controversial. We performed the present meta-analysis aiming to further investigate the potential relationship between VEGF polymorphisms and susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Polycystic Ovarian Syndrome (PCOS) in women is recognized as an endocrine disorder in reproductive-aged women 1 . PCOS is characterized by irregular menses, hyperandrogenism, micropolycystic ovaries and metabolic abnormalities 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic Ovarian Syndrome (PCOS) in women is recognized as an endocrine disorder in reproductive-aged women 1 . PCOS is characterized by irregular menses, hyperandrogenism, micropolycystic ovaries and metabolic abnormalities 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of seven studies showed there is little association between PCOS risk and the VEGF gene polymorphisms rs2010963, rs833061, and rs699947 in the general populations, whereas the genotype CC (rs2010963) might decrease the risk of PCOS among Asian women 8 . Another recent meta-analysis included 10 relevant case-control studies, involving 1347 PCOS cases and 1378 controls.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF gene is located in the chromosome region 6p21.3 5 . Single-nucleotide polymorphisms (SNPs) have been observed in the promoter, intronic, and untranslated regions of the VEGF gene, and several studies have suggested VEGF gene polymorphisms may be associated with PCOS risk [6][7][8] . VEGF rs833061 T and rs2010963 G alleles appear to correlate with altered VEGF expression levels.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced expression of PCNA in cystic follicles is accompanied by downregulation of the cystic fibrosis transmembrane conductance regulator, which is required for normal follicle development and causes abnormal follicular development in PCOS [ 33 ]. GCs are the main source of VEGF production [ 34 ]. VEGF is one of the major regulators of angiogenesis and plays an important role in multiple diseases affecting the ovary, such as PCOS.…”
Section: Research On Pcna In Gynecologymentioning
confidence: 99%